2010
DOI: 10.1111/j.1475-6811.2010.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles and relationship quality: Actual, perceived, and ideal partner matching

Abstract: Attachment dimension matching in dating relationships and how matching relates to relationship quality were investigated. Across 2 studies, individuals preferred similar but more secure partners (lower anxiety and lower avoidance) as reflected by their ideals. In Study 1, greater similarity between the self and perceptions of the partner's anxiety predicted more positive relationship outcomes (e.g., relationship satisfaction, trust). Similar results were found for ideal–perceived partner avoidance similarity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…As Meier et al (2013) have more recently demonstrated, perceived social support from a romantic partner could moderate symptoms of both depression and anxiety (Meier, Sharp, Michonski, Babcock, & Fitzgerald, 2013). At the same time, in the last thirty years, attachment theory has become one of the main references for the study of adult romantic relationships (Strauss, Morry, & Kito, 2012). In particular, attachment styles and, more specifically, Internal Working Models (IWMs) – the internalized representation of the self, of the other and of the possible reciprocal relationships – are considered an important factor in the achievement of a couple's adjustment (Carnelley, Hepper, Hicks, & Turner, 2011; Feeney, 1999; Holland & Roisman, 2010; Sadikaj, Moskowitz, & Zuroff, 2011; Zimmer-Gembeck & Ducat, 2010).…”
mentioning
confidence: 99%
“…As Meier et al (2013) have more recently demonstrated, perceived social support from a romantic partner could moderate symptoms of both depression and anxiety (Meier, Sharp, Michonski, Babcock, & Fitzgerald, 2013). At the same time, in the last thirty years, attachment theory has become one of the main references for the study of adult romantic relationships (Strauss, Morry, & Kito, 2012). In particular, attachment styles and, more specifically, Internal Working Models (IWMs) – the internalized representation of the self, of the other and of the possible reciprocal relationships – are considered an important factor in the achievement of a couple's adjustment (Carnelley, Hepper, Hicks, & Turner, 2011; Feeney, 1999; Holland & Roisman, 2010; Sadikaj, Moskowitz, & Zuroff, 2011; Zimmer-Gembeck & Ducat, 2010).…”
mentioning
confidence: 99%
“…On the one hand, there are some studies where the structural coupling hypothesis among secure individuals seems to have been confirmed, with little proof of romantic relationships which are characterized, even at the level of preference, from anxious-anxious and avoidant-avoidant coupling in respect to avoidant-ambivalent coupling (e.g. Collins & Reed, 1990;Kirkpatrick & Davis, 1994;Pietromonaco & Carnelley, 1994;Holmes & Johnson, 2009;Strauss et al 2012). On the other hand, other studies have shown inconsistencies in respect to the theory.…”
Section: From Behavioral Attachment System To Structural Couplingmentioning
confidence: 98%
“…For example, worry-prone individuals may seek out partners who can share worries or who can help to deal with them (e.g., by maintaining a reassuring calm façade). Relatedly, previous research suggests that people select romantic partners partly on the basis of perceived compatibility of attachment styles (e.g., Holmes & Johnson, 2009 ; Strauss, Morry, & Kito, 2012 ). However, like reverse causation, partner selection seems an implausible explanation for many of the partner effects reported above.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%